2023
DOI: 10.1038/s41598-023-31951-8
|View full text |Cite
|
Sign up to set email alerts
|

Bio-catalytic degradation of dibenzothiophene (DBT) in petroleum distillate (diesel) by Pseudomonas spp.

Abstract: Biodesulfurization (BDS) was employed in this study to degrade dibenzothiophene (DBT) which accounts for 70% of the sulfur compounds in diesel using a synthetic and typical South African diesel in the aqueous and biphasic medium. Two Pseudomonas sp. bacteria namely Pseudomonas aeruginosa and Pseudomonas putida were used as biocatalysts. The desulfurization pathways of DBT by the two bacteria were determined by gas chromatography (GC)/mass spectrometry (MS) and High-Performance Liquid Chromatography (HPLC). Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Several Pseudomonas species such as P. aeruginosa, P. stutzeri, P. putida, and Rhodococcus species such as R. erythropolis, and R. qingshengii IGTS8, were employed to degrade heterocyclic sulphur compounds [16][17][18][19][20]. Some of these biodegradation processes have low efficiencies which can be attributed to the inability of bacterial cells to be alive for a long time in a toxic aqueous medium of oil-water emulsions in the presence of 2-Hydroxybiphenyl and releases the sulphur content in form of sulphur dioxide [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Several Pseudomonas species such as P. aeruginosa, P. stutzeri, P. putida, and Rhodococcus species such as R. erythropolis, and R. qingshengii IGTS8, were employed to degrade heterocyclic sulphur compounds [16][17][18][19][20]. Some of these biodegradation processes have low efficiencies which can be attributed to the inability of bacterial cells to be alive for a long time in a toxic aqueous medium of oil-water emulsions in the presence of 2-Hydroxybiphenyl and releases the sulphur content in form of sulphur dioxide [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…21 Unlike aryl thioethers, DBTs are not very reactive and they account for the highest percentage of sulfur compounds found in heavy and vacuum gas oil that must be removed to meet environmental standards. 2,16,21,22 Interestingly, Garcia and coworkers have shown that Ni catalysts like [(dippe)-NiH)] 2 are great for the desulfurization of DBTs in the presence of alkyl Grignards. 23,24 While the system is believed to proceed through a classical Ni(0)/Ni(II) pathway, the sulfur gets converted initially to MgS and then to H 2 S after an acidic workup.…”
mentioning
confidence: 99%
“…This work highlights a rare example of using a Ni-doped DBA-POP to remove the C−S bonds from refractory sulfur compounds that are commonly found in heavy gas oil and vacuum gas oil. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]21,22 These investigations are necessary for developing innovative desulfurization catalytic systems that are recyclable and efficient at reducing the sulfur content in chemical fuels.…”
mentioning
confidence: 99%
See 2 more Smart Citations